2013
DOI: 10.3233/prm-130253
|View full text |Cite
|
Sign up to set email alerts
|

Grisel's syndrome: An unusual cause of Torticollis

Abstract: PURPOSE: The objective of this paper is to present a case series of patients with diagnosis of torticollis due to Grisel's syndrome and, in doing so, raise awareness of an unusual condition that could be fatal. A review of the literature is presented regarding diagnosis and treatment. METHODS: Case series of three patients that were 7, 10, and 12 years old with history of tonsillitis or neck surgery consulted to the service of Rehabilitation Medicine. RESULTS: Physical examination showed a fixed head or limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 14 publications
0
4
0
16
Order By: Relevance
“…2 Head and neck infections that have been reported preceding GS include pharyngitis, tonsillitis, infectious mononucleosis, and mastoiditis. [3][4][5][6] GS has also been reported after tonsillectomy and adenoidectomy. [7][8][9] The majority of cases present in children aged 5 to 12 years old 2,10-12 and can mimic other diagnoses such as meningitis, retropharyngeal abscess, painful lymphadenopathy, or trauma.…”
Section: Discussionmentioning
confidence: 95%
“…2 Head and neck infections that have been reported preceding GS include pharyngitis, tonsillitis, infectious mononucleosis, and mastoiditis. [3][4][5][6] GS has also been reported after tonsillectomy and adenoidectomy. [7][8][9] The majority of cases present in children aged 5 to 12 years old 2,10-12 and can mimic other diagnoses such as meningitis, retropharyngeal abscess, painful lymphadenopathy, or trauma.…”
Section: Discussionmentioning
confidence: 95%
“…While Ortiz and colleagues opted for fusion surgery in a case with hemiparesis, Missori et al described successful conservative therapy in a case presenting with transient visual loss due to vertebrobasilar compression. 26,30 There seems to be a general consensus toward conservative treatment in acute cases without neurological deficit and fusion in chronic cases, but these are not universal practices. 7,13,28,33,52 The duration of symptoms that define an "acute" or a "chronic" case varies among studies and makes direct comparisons challenging.…”
Section: Selection Of Patients For Nonsurgical Reductionmentioning
confidence: 99%
“…Prompt recognition and diagnosis of AARF is therefore critical, and neurosurgical consultation for all children presenting with torticollis has been recommended. 30…”
Section: Effect Of Symptom Duration Before Initial Intervention On Outcomesmentioning
confidence: 99%
“…However, surgical invasiveness and relatively high recurrence rate [ 9 , 10 ] were of concern in these treatment algorithms. Hence, even for chronic AARF, several studies have reported the efficacy of conservative treatments to reduce the invasiveness of the treatment, including rehabilitation [ 12 ], simple traction and bracing [ 13 ], halter traction and bracing [ 14 , 15 , 16 , 17 ], and closed manipulation under general anesthesia followed by external fixation [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%